PENGARUH INDEPENDENSI, KOMPETENSI, DAN SENSITIVITAS ETIKA PROFESI TERHADAP PRODUKTIVITAS KERJA AUDITOR EKSTERNAL (STUDI KASUS PADA AUDITOR PERWAKILAN BPK RI PROVINSI BALI - ARIYANTO, DODIK; MUTIA JATI, ARDANI (Jurnal Ilmiah Akuntansi dan Bisnis; Vol 5 No 2 (2010))
As the main actor in auditing, auditors must have independency,competency, willingness and sufficient work experiences, as well asprofessional ethics sensitivity. This research aims to examine the effect ofauditors’ independency, competency, and professional ethics sensitivity onproductivity rate of BPK’s auditors. Sample is determined using nonprobability sampling method, while analysis is conducted using method ofmultiple linear regressions. The result shows that the higher the level ofindependency, competency, and auditors’ ethics sensitivity the moreproductive the auditors are.
Keywords: independency, competency, sensitivity, professional ethics, productivity.